Risk of Depression Among MMT Patients: Does Coping Strategies and Perceived Social Support Play a Role? - Suzaily Wahab; Tee Chun Keat; Amirul Danial Azmi; Raynuha Mahadevan; Eni Rahaiza Muhamed Ramli; Law Kian Boon (SAGE Publishing, 2021)
Introduction: Patients receiving methadone maintenance therapy (MMT) experience higher level of stress and are at greater risk of developing mental health problems such as depression which could potentially affect both quality of life and treatment outcomes. This cross-sectional study is aimed at understanding the relationship between psychosocial factors such as social support, coping, and depression among patients receiving MMT in a Malaysian Hospital. Methods: One hundred and ninety-six patients attending MMT program were recruited. The Patient Health Questionnaire-9 (PHQ-9) was used to screen for depression, Multidimensional Scale of Perceived Social Support (MSPSS) was used to assess participants' perceived social support, and the Brief COPE questionnaire was used to assess coping strategies. The diagnosis of depression was made using Mini-International Neuropsychiatric Interview (MINI). Results: About 13.8% of our sample were diagnosed with depression. From our analysis, it was found that having higher levels of perceived social support (OR = 0.462, 95% CI 0.238-0.899, P  < .05), the use of active and emotion focused coping mechanism (OR = 0.231, 95% CI 0.095-0.565, P  < .005), and support seeking and self-distraction coping mechanism (OR = 0.196, 95% CI 0.074-0.521, P  < .001) was associated with lower likelihood of depression. On the contrary, the use of dysfunctional coping strategies such as denial, behavioral disengagement, and self-blame was associated with increased likelihood of depression (OR = 9.384, 95% CI 3.081-28.581, P  < .001). Conclusion: Active and emotion focused along with support and self-distraction coping strategies, and higher levels of perceived social support may serve as a buffer against depression in patients receiving MMT.